2012
DOI: 10.5251/abjna.2012.3.12.486.492
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of tree species diversity in Afi Mountain Wildlife Sanctuary, Southern Nigeria

Abstract: Appraisal of flora species which form an integral part of animal ecology, in wildlife based protected areas is necessary before any meaningful conservation work can commence. This informed the study on the preliminary assessment of tree species diversity in Afi Mountain Wildlife Sanctuary (AMWS) and its adjoining communal forest, a biodiversity hotspot in Nigeria. The Point Centre Quarter Method (PCQM) was employed for the study while the Shannon-Weiner Diversity Index (H) and student t test were used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
6
9
2
Order By: Relevance
“…Essentially, the H' values (obtained in the 3 sample plots) favourably compare with the values (3.69, 3.32 and 3.516) obtained in the three sites around Sengaltheri west Ghats as reported by Parthasarathy [19]. And 3.827 obtained by Aigbe, et al [13] in Afi river forest; and to 3.656, 3.621 and 3.342 obtained by Adekunle [20] for Shasha, Ala and Omo forest reserved respectively. Sampson (S) index with high species dominance indicates lower diversity [21]; unequivocally, a highly dissimilar tree species population would indicate higher diversity level more so, the species indices obtained here clearly implies that the sample plots are in fine fettle.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Essentially, the H' values (obtained in the 3 sample plots) favourably compare with the values (3.69, 3.32 and 3.516) obtained in the three sites around Sengaltheri west Ghats as reported by Parthasarathy [19]. And 3.827 obtained by Aigbe, et al [13] in Afi river forest; and to 3.656, 3.621 and 3.342 obtained by Adekunle [20] for Shasha, Ala and Omo forest reserved respectively. Sampson (S) index with high species dominance indicates lower diversity [21]; unequivocally, a highly dissimilar tree species population would indicate higher diversity level more so, the species indices obtained here clearly implies that the sample plots are in fine fettle.…”
Section: Discussionsupporting
confidence: 79%
“…This can be attributed to forest degradation activities which may have removal wider diameter at breast height (dbh) individuals as well as the fact that some large sized trees would have been removed though logging operation [14]. The dominant families (Arecaceae, Clusiaceae, Euphorbiaceae, Meliaceae, Moraceae, Gentianaceae, Rubiaceaceae, Phyllanthaceae, Apocynaceae and Annonaceae) in the sampled plots confirmed the claims of Akinyemi, et al [15]; Adekunle and Olagoke [16]; Humphrey and Godwin [7]; Edet, et al [13] and Ojo [17] among others who reported the prevalence of the members of Euphorbiaceae, Moraceae, Meliaceae, Clusiaceae, Rubiaceae and Gentimaceac families in the rainforest ecological zone of Nigeria. Perhaps the prevalence of I. gabonensis in the sample plot at Imringi is simply borne out by the facts that the species is preserved because of its economic values, and the strict penalty attached to illegal logging of the species [18].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Considering the impact of ever increasing anthropogenic pressure and development on forest resources, there is a need to assess forests from a biodiversity perspective to indicate conservation measures. Assessment of flora species which form an integral part of animal ecology, in wildlife based protected areas is necessary before any meaningful conservation work can commence (Edet & Ijeomah, 2012). Understanding species diversity is also important for helping managers to evaluate the complexity and resources of these forests (Jayakumar & Nair, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The result also shows that more plants species in less families were encountered in this survey than that by [18]. Furthermore, cash crop species in the study area include Musa paradiasica (3.21%), Theobroma cacoa (2.57%) and Musa sepientum (1.29%).…”
Section: Discussionmentioning
confidence: 66%